INTEGRATING ARTIFICIAL INTELLIGENCE AND DIGITAL LITERACY TO ENHANCE READING COMPREHENSION IN HIGHER EDUCATION: AN ENGLISH LANGUAGE TEACHING STUDY - Indria Selawati; Ayu Andriyaningsih; Vike Aprilianin Marwintaria Saputri; Dedi Kundana (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
The rapid development of artificial intelligence (AI) and the growing need for digital literacy have significantly transformed educational practices, particularly in enhancing students' reading comprehension skills. The integration of AI and digital literacy to improve reading comprehension in higher education remains a limited area of research. This study examines the impact of AI applications and digital literacy skills on the reading comprehension of Buddhist students in Bandar Lampung, specifically within Buddhist student activity units. The population consisted of 295 students, with 170 selected as the sample. Data were collected using a Likert-scale questionnaire and analyzed through multiple linear regression. The results indicate that both AI utilization and digital literacy contribute positively and complementarily to improving reading comprehension. Specifically, the AI variable showed a greater impact with a regression coefficient of 0.520 (p < 0.001), while digital literacy had a significant effect with a coefficient of 0.177 (p = 0.012). The integration of these two variables fosters a deeper and more meaningful learning process, enhancing not only academic achievement but also student independence and higher-order cognitive skills. These findings emphasize the importance of integrating AI tools and digital literacy as complementary learning strategies in higher education. This study provides empirical evidence of the significant role of technological innovation in enriching reading comprehension practices and promoting sustainable learning outcomes in the digital era. ABSTRAK Perkembangan pesat kecerdasan buatan (AI) dan meningkatnya kebutuhan literasi digital telah mengubah secara signifikan praktik pendidikan, terutama dalam meningkatkan keterampilan pemahaman bacaan siswa. Integrasi AI dan literasi digital untuk meningkatkan pemahaman bacaan di pendidikan tinggi masih merupakan area penelitian yang terbatas. Penelitian ini mengkaji dampak aplikasi AI dan keterampilan literasi digital terhadap pemahaman bacaan mahasiswa Buddha di Bandar Lampung, khususnya dalam unit kegiatan mahasiswa Buddha. Populasi penelitian terdiri dari 295 mahasiswa, dengan 170 di antaranya dipilih sebagai sampel. Data dikumpulkan menggunakan kuesioner skala Likert dan dianalisis melalui regresi linier berganda. Hasil penelitian menunjukkan bahwa baik pemanfaatan AI maupun literasi digital berkontribusi secara positif dan saling melengkapi untuk meningkatkan pemahaman bacaan. Secara spesifik, variabel AI menunjukkan dampak yang lebih besar dengan koefisien regresi sebesar 0,520 (p < 0,001), sementara literasi digital memiliki pengaruh signifikan dengan koefisien sebesar 0,177 (p = 0,012). Integrasi kedua variabel ini mendorong proses pembelajaran yang lebih mendalam dan bermakna, meningkatkan tidak hanya pencapaian akademik tetapi juga kemandirian siswa dan keterampilan kognitif tingkat tinggi. Temuan ini menekankan pentingnya mengintegrasikan alat AI dan literasi digital sebagai strategi pembelajaran yang saling melengkapi di pendidikan tinggi. Penelitian ini memberikan bukti empiris mengenai peran penting inovasi teknologi dalam memperkaya praktik pemahaman bacaan dan mendorong hasil pembelajaran yang berkelanjutan di era digital.